Binary and ternary capped In(Ga)As/GaAs self-assembled quantum dots: An annealing study. (May 2018) - Saha, Sumit; Hussain, Saddam; Kumar, Jitendra
Abstract: The effect of annealing time and annealing temperature on the binary (GaAs) and ternary (In0.15 Ga0.85 As) capped, single layer quantum dots (QDs) has been investigated theoretically. As-grown QDs are modeled as truncated pyramids with square base and energies and wave functions of the carriers confined in the structure have been calculated by solving three dimensional (3D) effective mass Schrödinger equations for electron and hole states using finite difference approximation. The effect of post-growth annealing has been modeled using Fick's second equation of diffusion. To make the situation more realistic, material compositions in the QD system have been considered in concurrence with experimental observations and strain has been incorporated as the deformation potential shift in the conduction and valence band. The results obtained using this simple theoretical model show very good agreement with experiments. A comparative analysis has been carried out between binary and ternary capped QD systems. A blue shift of the photoluminescence (PL) peak due to post-growth annealing has been observed for both of the cases where the PL energy shift is relatively smaller for ternary capped QD system compared to the binary capped QD system. The importance of using different capping layer compositions is discussed and usefulness of the present model for multi-layer QD systems has been established. Highlights: Binary and ternary capped, single layer quantum dots have been modeled theoretically. The effects of annealing time and annealing temperature have been investigated. The results show very good agreement with experiments. A comparative analysis has been carried out between binary and ternary capped QD systems. The importance of using different capping layer compositions is discussed.